PENDAMPINGAN PENGGUNAAN MEDIA SOSIAL YANG CERDAS DAN BIJAK BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Siti Nurul Intan Sari D; Sylvana Murni D HUTABARAT (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2020)
Humans as social beings are inseparable from interacting and communicating with other humans. Development of technology, make development the way of interaction humans being with social media. Social media as an alternative communication media for community to decrease the distance and the time is popular from children until adults especially housewives Problems with the use of social media among houswives who have been ensnared by legal cases have occurred alot, this can be seen from several cases both in print and other media. Therefore, the servants carry out cunselling and assistance to housewives in the service team partners RT.005, Kelurahan Ciganjur, Kecamatan Jagakarsa, Jakarta Selata, to change the understandings of housewives in using social media intelligently and wisely based on Rules of Electronic Information and Transactions.The participation of the partner in this service to providethe tools and information needed for the service to make well. The method of this assistance used communication and dialogues with the target community throught extension activities and finally a simulation activity is caried out to the test increase in participant understanding. This community service provides results in the form of increased knowledge and understanding of participants, namely housewives about the use of wise and intelligent social media in their daily lives based on the information and electronic transaction act so that the use of social media can provide benefits rather than bring their users caught in legal cases.